Hydrothermal synthesis of reduced graphene oxide-cellulose composites for supercapacitor application - Mäkinen, Salla (My University, 2025)
In the modern world, there is an ever-rising demand for new, environmentally friendly and cost-effective solutions for energy storage. Carbon based materials like reduced graphene oxide (rGO) shows promising features for supercapacitor application due toits high surface area, electrical conductivity and chemical stability. To reduce the precursor graphene oxide, without toxic chemicals, a hydrothermal method was used in an inert atmosphere at low temperatures. Our efforts have resulted in a specific capacitance of 199 F/g at 0.25 A/g in 1 M H2SO4 for hydrothermally reduced rGO. To compare the performance of the hydrothermal method, chemical and microwave reduction methods were also used and studied using UV-Vis spectroscopy, and electrochemical measurements. A green and sustainable composite combining the conductivity of rGO and mechanical strength of cellulose nanofibers was prepared by a simple sonication-assisted combination process, resulting in a specific capacitance of 167 F/g at 0.25 A/g in 1 M H2SO4. Self-standing flexible composite films were prepared using vacuum filtration and characterized using XRD and 4-probe conductivity measurements.
Keywords: reduced graphene oxide, hydrothermal reduction, chemical reduction, microwave reduction, nanocellulose, electrochemistry, supercapacitor